Herpes Simplex Virus Hepatitis in an Immunocompetent Host Resembling Hepatic Pyogenic Abscesses. (30th October 2016) - Down, Carrie; Mehta, Amit; Salama, Gayle; Hissong, Erika; Rosenblatt, Russell; Cantor, Michael; Helfgott, David; Marks, Kristen
Abstract : Herpes simplex virus (HSV) hepatitis represents a rare complication of HSV infection, which can progress to acute liver failure and, in some cases, death. We describe an immunocompetent 67-year-old male who presented with one week of fever and abdominal pain. Computed tomography (CT) scan and magnetic resonance imaging (MRI) of the abdomen showed multiple bilobar hepatic lesions, some with rim enhancement, compatible with liver abscesses. Subsequent liver biopsy, however, revealed hepatocellular necrosis, HSV-type intranuclear inclusions, and immunostaining positive for herpes virus type 2 (HSV-2). Though initially treated with broad-spectrum antibiotics, following histologic diagnosis of HSV hepatitis, the patient was transitioned to intravenous acyclovir for four weeks and he achieved full clinical recovery. Given its high mortality and nonspecific presentation, one should consider HSV hepatitis in all patients with acute hepatitis with multifocal hepatic lesions of unknown etiology. Of special note, this is only the second reported case of HSV liver lesions mimicking pyogenic abscesses on CT and MRI.